The Effect of Using De-contextualization and Semi-Contextualization Teaching Techniques on Turkish EFL Learners’ Vocabulary Learning - Yeganehpour, Parisa; Zarfsaz, Elham (LPPM Universitas Advent Indonesia, 2022)
We are now surrounded by information from television, the internet, and digital media. Multimedia connects us to diverse languages and civilizations. The usage of a variety of forms of multimedia has a number of advantages for foreign language acquisition. The purpose of this study was to determine the extent to which using television programs and subtitled television shows as semi-contextualized strategies aids vocabulary retention during language acquisition. This research was performed at a Turkish government university. The teacher divided the classes into two experimental groups ranging in age from 18-20. The research began with the administration of a pretest. Then, the newly concentrated terms were taught using two distinct teaching techniques: decontextualized and semi-contextualized instruction. The study was conducted during a semester in 14 sessions. After teaching the new terms using the two strategies, an instant post-test was conducted at the end of sessions. A delayed post-test was conducted three sessions later. Following that, the participants' scores were statistically examined. The study's findings indicated that there were no significant differences in vocabulary teaching strategies between semi-contextualized (TV program) and decontextualized (board monitoring). It should be emphasized that the researchers, as English teacher, anticipated differences between two strategies (preference for semi-contextualized technique) based on their own teaching experience.